Sistem Pendukung Keputusan Pemilihan Santri Terbaik Dengan Pendekatan Weighted Product - Aliy Hafiz; Ifo Wahyu Pratama; Beti Susilawati; Sulastri; Bambang Suprapto (Prosiding SISFOTEK, 2021)
Santri is a term for someone who is doing education in a boarding school. every year an event is held for students who graduate from their educational activities. the management of the boarding school will choose the best students each year they graduate. To find the best students needed more because of the criteria needed. The decision support system provides an alternative in determining who the best students will be. Due to the nature of the decision support system that is objective, fast, accurate and computer-based, making it easier to select the best students. The Weighted Product method is part of the concept of Fuzzy Multi-Attribute Decision Making (FMADM) where a normalization process is needed in calculating the normalization. This method specifically calculates the weight of the value in each of the existing criteria. This decision support system is a solution tool that can provide solutions that can assist in the process of selecting the best students computerized to be more effective and efficient. The results of the study prove that this application is able to help companies in the process of selecting the best students with product weighting methods, as well as providing information on the best students effectively and efficiently.